CHARACTERIZATION OF A GUMBORO DISEASE OUTBREAK IN A POULTRY FARM OF HAVANA - Grandía G., Raiden (2014)
The objective of the study was to characterize a Gumboro disease outbreak in apoultry farm of Havana, Cuba in 2010. A population of 2959 broilers was studied. Breedingmanagement, clinical observations and anatomopathological findings were analyzed.The morbidity, mortality and lethality rates were calculated. Necropsy was done in 40 birds with signs of illness for the histopathological study of the bursa of Fabricius,thymus and spleen. The presence of virus antigens in bursal macerated was conductedby an AC-ELISA. The study showed 5.1% mortality, 8.4% morbidity, and 60.6% lethality.The most frequent clinical sign was general depression (100%) and macroscopic lesionswere hemorrhagic bursitis, edema of the bursa and nephritis (85-90%). Follicular lymphoiddepletion in bursa was found in the histopathology. The AC-ELISA showed that 82.5%of bursas were positive. Vaccination and biosecurity deficiencies conditioned theoccurrence of the Gumboro disease outbreak, causing economic losses in the farm.